Stionic influences on physiology, growth and yield attributes inmango (Mangifera indica L.) - Sharma, N; Singh, S.K.; Dahuja, A; Rana, V. S.; Mishra, G. P.; Prakash, J; Singh, N; Sharma, R M; Dubey, A. K.; Shivran, M; Gutam, S (Journal of Horticultural Sciences, 2026)
The present experiment was carried out to study the influence of the rootstocks (PAM-2, Kurukkan, Olour, K3, PAM-1) on scion cultivars (Pusa Arunima, Pusa Surya and Amrapali) based on the physiological traits, growth parameters, and yield attributes. The maximum yield (80.46 kg tree-1), number of fruits (484.33), and transpiration rate (15.04 μmol H2O m-2s-1) were found in the Amrapali/Kurukkan combination. Highest photosynthetic rate (10.62 μmol CO2 m-2s-1) and total chlorophyll (2.03 mg/g) were found in Amrapali/Olour combination. The maximum fruiting density (3.72 m3), and yield efficiency (0.525 cm2 TCSA) were found in the Amrapali/PAM-1 combination. Canopy volume (247.31 m3), and TCSA (358.48 cm2) were found to be highest in Pusa Arunima/Olour and lowest in Pusa Surya/PAM-1 (72.24 m3 , 147.46 cm2), respectively. The findings indicated that Olour rootstock was promising for yield and PAM-1 was superior for yield efficiency.